High-surface tension polyethylene filled master batch as well as preparation method and application thereof
By combining modified polyethylene resin and ultrafine heavy calcium, combined with melt blending modification and cooling kneading extrusion technology, the surface tension of polyethylene filled masterbatch is improved, and the low surface tension of polyethylene filled masterbatch is solved. The problem has significantly improved the surface tension and ink absorption of HDPE waterproof coils.
Patent Information
- Application Number
- CN202411284337.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
AI Technical Summary
The surface tension of polyethylene-filled masterbatch is low, which affects the ink absorption and finished product dynamism of its application in HDPE waterproof coils. The existing corona discharge treatment method is unstable and difficult to effectively apply in production.
The melt blending and cooling kneading extrusion process is carried out by using a combination of modified polyethylene resin, ultrafine heavy calcium, surfactant and compatible agent in the production process of polyethylene filler masterbatches to improve filling The surface tension of the masterbatch reduces the amount of low-surface tension processing aids, and uses ultraviolet rays to increase the molecular weight of the low molecular layer on the PE surface.
The surface tension of HDPE polymer waterproof coil is significantly improved, and the dyne value can reach 38dyn/cm, which is better than traditional polyethylene filled masterbatches, ensuring that the mechanical properties and resistance meet the standard requirements.
Smart Images

Figure CN119119672A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filling masterbatches, and in particular to a high surface tension polyethylene filling masterbatch and a preparation method and application thereof. Background Art
[0002] Polyethylene is a non-polar material with low surface energy, hydrophobic and inert surface. It has poor adhesion, antistatic and hydrophilic properties, and poor compatibility with polar polymers or inorganic fillers. Therefore, the surface energy of PE filler masterbatch prepared with polyethylene as the carrier resin is generally low. When applied to downstream HDPE waterproofing membranes, the dyne value of the finished product is low, which affects the ink absorption of downstream products. At present, the surface energy is mainly improved by corona discharge treatment. The effect of this treatment method is unstable, and sometimes the treatment effect disappears after being left for a few days, which is extremely inconvenient for daily production. If the surface tension of the masterbatch can be increased during the production process of the filler masterbatch, thereby increasing the surface tension of the HDPE waterproofing membrane in downstream applications, it will bring great convenience to downstream production.
[0003] In order to meet market demand, a polyethylene filling masterbatch with high surface tension is developed and applied in HDPE polymer waterproof membrane to effectively improve the surface tension of the membrane, which is of great significance. Summary of the invention
[0004] The purpose of the present invention is to provide a high surface tension polyethylene filling masterbatch and a preparation method and application thereof in order to overcome the deficiencies of the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a high surface tension polyethylene filling masterbatch, which comprises the following raw materials in mass fraction:
[0007] Modified polyethylene resin 8-10%, ultrafine calcium carbonate 85-88%, surfactant 0.5-1.5%, coupling agent 1-2%, compatibilizer 0.8-1.0%;
[0008] The preparation method of the modified polyethylene resin comprises the following steps: mixing polyethylene resin, maleic anhydride and an initiator, and then performing melt blending modification to obtain the modified polyethylene resin.
[0009] Preferably, the mass of the maleic anhydride is 3-5% of the mass of the polyethylene resin, and the mass of the initiator is 0.3-1% of the mass of the polyethylene resin; the polyethylene resin is a linear low-density polyethylene resin; and the initiator is dicumyl peroxide.
[0010] Preferably, the mixing temperature is 100-120°C, the mixing time is 3-5 min, the mixing speed is 450-550 r / min; and the temperature of the melt blending modification is 185-195°C.
[0011] Preferably, the particle size of the ultrafine calcium carbonate is ≤5 μm, and the oil absorption value is 22-24; the surfactant is cerium stearate, iron stearate or N,N-dibutyl dithiocarbamate iron.
[0012] Preferably, the coupling agent comprises N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and isopropoxy tri(dodecylbenzenesulfonyloxy) titanate; the mass ratio of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane to isopropoxy tri(dodecylbenzenesulfonyloxy) titanate is 1:3-5;
[0013] The compatibilizer comprises oxidized polyethylene wax and maleic anhydride grafted polyethylene wax, and the mass ratio of the oxidized polyethylene wax to the maleic anhydride grafted polyethylene wax is 2-4:1.
[0014] Preferably, the acid value of the oxidized polyethylene wax is 15-20 mg KOH / g, the viscosity is 110-170 mPa·s, and the molecular weight of the maleic anhydride grafted polyethylene wax is 4000-8000.
[0015] The present invention also provides a method for preparing the high surface tension polyethylene filling masterbatch, comprising the following steps:
[0016] 1) mixing ultrafine heavy calcium, a surfactant, a coupling agent and a compatibilizer to obtain a mixture;
[0017] 2) mixing the mixture with a modified polyethylene resin to obtain a mixed material;
[0018] 3) The mixed material is sequentially cooled, mixed and extruded, and water-ring hot cut to obtain a high surface tension polyethylene filling masterbatch.
[0019] Preferably, in step 1), the ultrafine heavy calcium is preheated before mixing, the preheating temperature is 100-120° C., the preheating time is 5-10 min, and the preheating speed is 450-550 r / min;
[0020] Step 1) The mixing temperature is 100-110° C., the mixing time is 15-20 min, and the mixing speed is 550-650 r / min.
[0021] Preferably, the mixing temperature in step 2) is 110-120° C., the mixing time is 20-30 min, and the mixing speed is 750-850 r / min;
[0022] Step 3) The cooling time is 5 to 10 minutes, the rotation speed during the cooling process is 370 to 430 r / min; the mixing and extrusion temperature is 180 to 190°C.
[0023] The present invention also provides application of the high surface tension polyethylene filling masterbatch in high-density polyethylene polymer waterproofing coiled material.
[0024] The beneficial effects of the present invention include the following:
[0025] 1) The present invention grafts maleic anhydride and DCP to modify polyethylene resin to improve the surface tension of the resin itself, and uses ultrafine heavy calcium with low oil absorption produced by a vertical mill secondary classification process as filler, which can effectively reduce the amount of low surface tension processing aids (PE wax, stearic acid, etc.) added. At the same time, the polarity of high acid value oxidized polyethylene wax is strong, which can improve the surface tension of the filling masterbatch. Then, a small amount of photosensitizer is used as a surfactant, and ultraviolet rays are used to increase the molecular weight of the low molecular layer on the surface of PE, thereby improving the tension of the solid surface, and finally a high surface tension polyethylene filling masterbatch is obtained.
[0026] 2) The high surface tension polyethylene filling masterbatch of the present invention is applied to downstream high-density polyethylene (HDPE) polymer waterproof membrane. While ensuring that various mechanical properties and durability meet the requirements of relevant standards, the dyne value can reach 38dyn / cm, which is significantly better than traditional polyethylene filling masterbatch, and effectively improves the surface tension of HDPE polymer waterproof membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a process flow chart for preparing high surface tension polyethylene filling masterbatch. DETAILED DESCRIPTION
[0028] The present invention provides a high surface tension polyethylene filling masterbatch, which comprises the following raw materials in mass fraction:
[0029] Modified polyethylene resin 8-10%, ultrafine calcium carbonate 85-88%, surfactant 0.5-1.5%, coupling agent 1-2%, compatibilizer 0.8-1.0%;
[0030] The preparation method of the modified polyethylene resin comprises the following steps: mixing polyethylene resin, maleic anhydride and an initiator, and then performing melt blending modification to obtain the modified polyethylene resin.
[0031] The high surface tension polyethylene filling masterbatch of the present invention contains 8 to 10% of modified polyethylene resin, preferably 8.5 to 9.5%, and more preferably 9%.
[0032] In the preparation method of the modified polyethylene resin of the present invention, the mass of the maleic anhydride is preferably 3-5% of the mass of the polyethylene resin, more preferably 3.5-4.5%, and more preferably 4%; the mass of the initiator is preferably 0.3-1% of the mass of the polyethylene resin, more preferably 0.5-0.8%, and more preferably 0.6-0.7%; the polyethylene resin is preferably a linear low-density polyethylene resin; and the initiator is preferably dicumyl peroxide (DCP).
[0033] In the present invention, if the amount of initiator added is too large, although the grafting rate is high, the side reactions increase, that is, the self-crosslinking reaction of the polyethylene resin increases, which leads to a sharp decrease in the melt flow rate of the grafted resin, affecting the processing performance of the product.
[0034] In the present invention, mixing is preferably carried out in a high mixer, and the mixed materials are melt-blended and modified in a twin-screw extruder; the aspect ratio of the twin-screw extruder is preferably 47-49:1, more preferably 48:1, and the rotation speed of the twin-screw extruder is preferably 100-150r / min, more preferably 110-140r / min, and more preferably 120-130r / min; when the rotation speed of the twin-screw extruder is too fast, the material stays in the screw for a short time, the reaction fails to fully occur, the grafting rate is low, and the thermal shear of the material in the screw is also stronger, which easily leads to self-crosslinking of the polyethylene.
[0035] In the preparation method of the modified polyethylene resin of the present invention, the mixing temperature is preferably 100-120°C, more preferably 105-115°C, more preferably 110°C, the mixing time is preferably 3-5min, more preferably 4min, the mixing speed is preferably 450-550r / min, more preferably 480-520r / min, more preferably 500r / min; the temperature of the melt blending modification is preferably 185-195°C, more preferably 188-192°C, more preferably 190°C.
[0036] In the present invention, the materials modified by melt blending are sequentially cold pressed, air cooled and ground, and then collected to obtain modified polyethylene resin.
[0037] The high surface tension polyethylene filling masterbatch of the present invention contains 85-88% of ultrafine heavy calcium, preferably 86-87%, and more preferably 86.5%.
[0038] In the present invention, the particle size of the ultrafine heavy calcium is preferably ≤5μm, the content of particles below 1μm in the ultrafine heavy calcium is ≤5%, the content of particles below 2μm is ≤38%, D97 is 5±0.5μm, and D50 is 2.5±0.1μm; the oil absorption value of the ultrafine heavy calcium is preferably 22-24, and more preferably 23.
[0039] The oil absorption value of the ultrafine heavy calcium carbonate of the present invention is lower than that of the common 2500 mesh heavy calcium carbonate products. When used in filling masterbatch, the addition amount of low surface tension processing aids (PE wax, stearic acid, etc.) can be reduced.
[0040] In the present invention, the ultrafine heavy calcium is produced by a secondary classification vertical mill process, and the submicron particles in the ultrafine heavy calcium are separated out by the secondary classification process.
[0041] The high surface tension polyethylene filling masterbatch of the present invention contains 0.5 to 1.5% of a surfactant, preferably 0.8 to 1.2%, and more preferably 1%.
[0042] In the present invention, the surfactant is preferably cerium stearate, iron stearate or N,N-dibutyldithiocarbamate iron.
[0043] In the present invention, the presence of the surfactant (photosensitizer) can utilize ultraviolet rays to increase the molecular weight of the low molecular layer on the surface of polyethylene, thereby increasing the tension of the solid surface.
[0044] The high surface tension polyethylene filling masterbatch of the present invention contains 1 to 2% of coupling agent, preferably 1.2 to 1.8%, and more preferably 1.4 to 1.5%.
[0045] In the present invention, the coupling agent preferably comprises N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and isopropoxytri(dodecylbenzenesulfonyloxy)titanate; the mass ratio of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and isopropoxytri(dodecylbenzenesulfonyloxy)titanate is preferably 1:3-5, more preferably 1:3.5-4.5, and more preferably 1:4.
[0046] The high surface tension polyethylene filling masterbatch of the present invention contains 0.8-1.0% of a compatibilizer, preferably 0.85-0.95%, and more preferably 0.9%.
[0047] In the present invention, the compatibilizer preferably comprises oxidized polyethylene wax and maleic anhydride grafted polyethylene wax, and the mass ratio of oxidized polyethylene wax to maleic anhydride grafted polyethylene wax is preferably 2-4:1, more preferably 2.5-3.5:1, and more preferably 3:1.
[0048] In the present invention, the acid value of the oxidized polyethylene wax is preferably 15 to 20 mg KOH / g, more preferably 16 to 19 mg KOH / g, more preferably 17 to 18 mg KOH / g, the viscosity is preferably 110 to 170 mPa·s, more preferably 120 to 160 mPa·s, more preferably 130 to 150 mPa·s, and the molecular weight of the maleic anhydride grafted polyethylene wax is preferably 4000 to 8000, more preferably 5000 to 7000, more preferably 6000.
[0049] In the present invention, the high acid value oxidized polyethylene wax has a strong polarity and can increase the surface tension of the polyethylene filling masterbatch.
[0050] The present invention also provides a method for preparing the high surface tension polyethylene filling masterbatch, comprising the following steps:
[0051] 1) mixing ultrafine heavy calcium, a surfactant, a coupling agent and a compatibilizer to obtain a mixture;
[0052] 2) mixing the mixture with a modified polyethylene resin to obtain a mixed material;
[0053] 3) The mixed material is sequentially cooled, mixed and extruded, and water-ring hot cut to obtain a high surface tension polyethylene filling masterbatch.
[0054] In step 1) of the present invention, the ultrafine heavy calcium carbonate is preferably preheated before mixing, and the preheating temperature is preferably 100-120°C, more preferably 105-115°C, and more preferably 110°C; the preheating time is preferably 5-10 min, more preferably 6-9 min, and more preferably 7-8 min; the preheating speed is preferably 450-550 r / min, more preferably 470-520 r / min, and more preferably 490-500 r / min.
[0055] In the present invention, the mixing temperature in step 1) is preferably 100-110°C, more preferably 102-108°C, and more preferably 104-105°C; the mixing time is preferably 15-20min, more preferably 16-19min, and more preferably 17-18min; the mixing speed is preferably 550-650r / min, more preferably 570-620r / min, and more preferably 590-600r / min.
[0056] In the present invention, the mixing temperature in step 2) is preferably 110-120°C, more preferably 112-118°C, and more preferably 114-115°C; the mixing time is preferably 20-30min, more preferably 22-28min, and more preferably 24-25min; the mixing speed is preferably 750-850r / min, more preferably 780-820r / min, and more preferably 800r / min;
[0057] The cooling time of step 3) is preferably 5 to 10 min, more preferably 6 to 9 min, and more preferably 7 to 8 min; the rotation speed during the cooling process is preferably 370 to 430 r / min, more preferably 380 to 420 r / min, and more preferably 400 to 410 r / min; the temperature of the mixing extrusion is preferably 180 to 190°C, more preferably 182 to 188°C, and more preferably 184 to 185°C.
[0058] In the present invention, after the water ring hot cutting in step 4) is completed, dehydration vibration and wind drying are sequentially performed to collect and obtain the high surface tension polyethylene filling masterbatch.
[0059] The process flow chart of the present invention for preparing high surface tension polyethylene filling masterbatch is as follows: Figure 1 shown.
[0060] The present invention also provides application of the high surface tension polyethylene filling masterbatch in high-density polyethylene polymer waterproofing coiled material.
[0061] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0062] In the embodiment, the grade of linear low-density polyethylene resin (LLDPE resin) is DFDA-7042, the aspect ratio of the 1# twin-screw extruder is 48:1, the aspect ratio of the 2# twin-screw extruder is 60:1, and the diameter is 73 mm; the ultrafine heavy calcium is produced by a secondary classification vertical mill process, and the ultrafine heavy calcium has a particle content of less than 1 μm and a particle content of less than 2 μm and a particle content of less than 38%, D97 is 5±0.5 μm, and D50 is 2.5±0.1 μm; the grade of oxidized polyethylene wax is OW-0526-20, and the grade of maleic anhydride grafted polyethylene wax is AC 573A.
[0063] Example 1
[0064] The high surface tension polyethylene filler masterbatch comprises the following raw materials in mass fraction: 9% of modified polyethylene resin, 88% of ultrafine calcium carbonate, 0.5% of surfactant (cerium stearate), 1.7% of coupling agent, and 0.8% of compatibilizer; in the coupling agent, the mass ratio of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and isopropoxytri(dodecylbenzenesulfonyloxy)titanate is 1:3; in the compatibilizer, the mass ratio of OW-0526-20 and A-C573A is 2:1, the acid value of OW-0526-20 is 16 mg KOH / g, the viscosity is 120 mpa·s, and the molecular weight of AC 573A is 5000.
[0065] The LLDPE resin, maleic anhydride and initiator DCP are transported into the No. 1 high-speed mixer for mixing through the automatic metering system. The addition amounts of maleic anhydride and DCP account for 3% and 0.3% of the mass of the LLDPE resin, respectively. The temperature of the high-speed mixer is 110° C., the speed of the mixer is 500 r / min, and the mixing time is 4 min. After the high-speed mixing is completed, the materials enter the No. 1 twin-screw extruder for melt blending modification. The temperature of the extruder is 185° C., and the speed of the extruder is 120 r / min. After cold pressing, air cooling and coarse crushing, the modified LLDPE resin is crushed by an air mill and collected for later use.
[0066] The ultrafine heavy calcium carbonate (oil absorption value is 22) is conveyed by wind through the pipeline into the 2# high-speed mixer, and the ultrafine heavy calcium carbonate is preheated. The material temperature is 100°C, the mixer speed is 500r / min, and the mixing time is 5min. After the ultrafine heavy calcium carbonate is preheated, coupling agent, compatibilizer and surfactant are added to the 2# high-speed mixer, and high-speed stirring is carried out at a speed of 600r / min and 100°C for 15min. The modified LLDPE resin powder is added through the automatic feeding system and continued to be stirred. The mixer speed is 800r / min, the material temperature is 110°C, and the stirring time is 20min. The material in the 2# high-speed mixer is transported into the cold mixer for stirring and cooling treatment. The mixer speed is 400r / min and the stirring time is 5min. After cooling, the material is transported to the silo for standby use. The material in the silo enters the 2# twin-screw extruder for mixing and extrusion. The extruder temperature is 180℃ and the extruder speed is 120r / min. After water ring hot cutting, dehydration vibration, wind drying, collection, and entering the finished product silo.
[0067] Example 2
[0068] The high surface tension polyethylene filler masterbatch comprises the following raw materials in mass fraction: 9% of modified polyethylene resin, 87.1% of ultrafine heavy calcium, 1.5% of surfactant (ferric stearate), 1.5% of coupling agent, and 0.9% of compatibilizer; in the coupling agent, the mass ratio of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and isopropoxytri(dodecylbenzenesulfonyloxy)titanate is 1:4; in the compatibilizer, the mass ratio of OW-0526-20 and AC 573A is 3:1, the acid value of OW-0526-20 is 18 mgKOH / g, the viscosity is 160 mPa·s, and the molecular weight of AC 573A is 7000.
[0069] The LLDPE resin, maleic anhydride and initiator DCP are transported to the No. 1 high-speed mixer for mixing through an automatic metering system. The addition amounts of maleic anhydride and DCP account for 4% and 0.7% of the mass of the LLDPE resin, respectively. The temperature of the high-speed mixer is 110° C., the speed of the mixer is 500 r / min, and the mixing time is 3 min. After the high-speed mixing is completed, the materials enter the No. 1 twin-screw extruder for melt blending modification. The temperature of the extruder is 190° C., and the speed of the extruder is 130 r / min. After cold pressing, air cooling, and coarse crushing, the modified LLDPE resin is crushed by an air mill and collected for later use.
[0070] The ultrafine heavy calcium (oil absorption value is 23) is transported by wind through the pipeline into the 2# high-speed mixer, and the ultrafine heavy calcium is preheated. The material temperature is 110℃, the mixer speed is 500r / min, and the mixing time is 7min. After the ultrafine heavy calcium is preheated, the coupling agent, compatibilizer and surfactant are added to the 2# high-speed mixer, and the high-speed stirring is carried out at 600r / min and 105℃ for 17min. The modified LLDPE resin powder is added through the automatic feeding system and continued to be stirred. The mixer speed is 800r / min, the material temperature is 115℃, and the stirring time is 25min. The material in the 2# high-speed mixer is transported into the cold mixer for stirring and cooling treatment. The mixer speed is 400r / min and the stirring time is 7min. After cooling, the material is transported to the silo for standby. The material in the silo enters the 2# twin-screw extruder for mixing and extrusion. The extruder temperature is 185℃. After water ring hot cutting, dehydration vibration, wind drying, collection, and entering the finished product silo.
[0071] Example 3
[0072] The high surface tension polyethylene filler masterbatch comprises the following raw materials in mass fraction: 10% of modified polyethylene resin, 86.5% of ultrafine heavy calcium, 0.5% of surfactant (N,N-dibutyl dithiocarbamate iron), 2% of coupling agent, and 1% of compatibilizer; in the coupling agent, the mass ratio of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and isopropoxytri(dodecylbenzenesulfonyloxy)titanate is 1:5; in the compatibilizer, the mass ratio of OW-0526-20 and AC 573A is 4:1, the acid value of OW-0526-20 is 17 mg KOH / g, the viscosity is 150 mpa·s, and the molecular weight of AC 573A is 6000.
[0073] The LLDPE resin, maleic anhydride and initiator DCP are transported to the No. 1 high-speed mixer for mixing through an automatic metering system. The addition amounts of maleic anhydride and DCP account for 5% and 1% of the mass of the LLDPE resin, respectively. The temperature of the high-speed mixer is 120° C., the speed of the mixer is 500 r / min, and the mixing time is 5 min. After the high-speed mixing is completed, the materials enter the No. 1 twin-screw extruder for melt blending modification. The temperature of the extruder is 195° C., and the speed of the extruder is 140 r / min. After cold pressing, air cooling, and coarse crushing, the modified LLDPE resin is crushed by an air mill and collected for later use.
[0074] The ultrafine heavy calcium (oil absorption value is 24) is transported by wind through the pipeline into the 2# high-speed mixer, and the ultrafine heavy calcium is preheated. The material temperature is 120℃, the mixer speed is 500r / min, and the mixing time is 10min. After the ultrafine heavy calcium is preheated, the coupling agent, compatibilizer and surfactant are added to the 2# high-speed mixer, and the high-speed stirring is carried out at 600r / min and 110℃ for 20min. The modified LLDPE resin powder is added through the automatic feeding system and continued to stir. The mixer speed is 800r / min, the material temperature is 120℃, and the stirring time is 30min. The material in the 2# high-speed mixer is transported into the cold mixer for stirring and cooling treatment. The mixer speed is 400r / min and the stirring time is 10min. After cooling, the material is transported to the silo for standby. The material in the silo enters the 2# twin-screw extruder for mixing and extrusion. The extruder temperature is 190℃. After water ring hot cutting, dehydration vibration, wind drying, collection, and entering the finished product silo.
[0075] The high surface tension polyethylene filling masterbatch prepared in Examples 1 to 3 and the traditional polyethylene filling masterbatch of the comparative example were respectively applied to the HDPE polymer waterproof membrane, which was made of the following raw materials in parts by weight: 30 parts of HDPE, 30 parts of ethylene-vinyl acetate copolymer (EVA), 20 parts of ethylene propylene rubber (EPDM), 15 parts of filling masterbatch, 1.5 parts of auxiliary antioxidant (antioxidant 168), 1 part of antioxidant (antioxidant 101), and 4 parts of ultraviolet light absorber (UV-531), and tested according to GB / T 23457-2017 standard. The test results are shown in Table 1.
[0076] Table 1 Performance of HDPE polymer waterproofing membranes prepared in Examples and Comparative Examples
[0077]
[0078] It can be seen from Table 1 that the high surface tension polyethylene filling masterbatch obtained by the preparation method of the present invention is applied to HDPE polymer waterproof membrane. While ensuring that various mechanical properties and durability meet the requirements of relevant standards, its dyne value can reach 38dyn / cm, which is significantly better than the traditional filling masterbatch, and effectively improves the surface tension of the HDPE polymer waterproof membrane.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high surface tension polyethylene filling masterbatch, characterized in that: High surface tension polyethylene filler masterbatch contains the following raw materials by mass fraction: Modified polyethylene resin 8-10%, ultrafine calcium carbonate 85-88%, surfactant 0.5-1.5%, coupling agent 1-2%, compatibilizer 0.8-1.0%; The preparation method of the modified polyethylene resin comprises the following steps: mixing polyethylene resin, maleic anhydride and an initiator, and then performing melt blending modification to obtain the modified polyethylene resin.
2. The high surface tension polyethylene filling masterbatch according to claim 1, characterized in that: The mass of the maleic anhydride is 3-5% of the mass of the polyethylene resin, and the mass of the initiator is 0.3-1% of the mass of the polyethylene resin; the polyethylene resin is a linear low-density polyethylene resin; and the initiator is diisopropylbenzene peroxide.
3. The high surface tension polyethylene filling masterbatch according to claim 1 or 2, characterized in that: The mixing temperature is 100-120°C, the mixing time is 3-5 minutes, and the mixing speed is 450-550 r / min; the temperature of the melt blending modification is 185-195°C.
4. The high surface tension polyethylene filling masterbatch according to claim 1, characterized in that: The particle size of the ultrafine heavy calcium is ≤5 μm, and the oil absorption value is 22-24; the surfactant is cerium stearate, iron stearate or N,N-dibutyl dithiocarbamate iron.
5. The high surface tension polyethylene filling masterbatch according to claim 1 or 4, characterized in that: The coupling agent comprises N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane and isopropoxy tri(dodecylbenzenesulfonyloxy) titanate; the mass ratio of N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane to isopropoxy tri(dodecylbenzenesulfonyloxy) titanate is 1:3-5; The compatibilizer comprises oxidized polyethylene wax and maleic anhydride grafted polyethylene wax, and the mass ratio of the oxidized polyethylene wax to the maleic anhydride grafted polyethylene wax is 2-4:
1.
6. The high surface tension polyethylene filling masterbatch according to claim 5, characterized in that: The acid value of the oxidized polyethylene wax is 15-20 mg KOH / g, the viscosity is 110-170 mPa·s, and the molecular weight of the maleic anhydride grafted polyethylene wax is 4000-8000.
7. The method for preparing the high surface tension polyethylene filler masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are included: 1) mixing ultrafine heavy calcium, a surfactant, a coupling agent and a compatibilizer to obtain a mixture; 2) mixing the mixture with a modified polyethylene resin to obtain a mixed material; 3) The mixed material is sequentially cooled, mixed and extruded, and water-ring hot cut to obtain a high surface tension polyethylene filling masterbatch.
8. The preparation method according to claim 7, characterized in that: In step 1), the ultrafine heavy calcium is preheated and then mixed, the preheating temperature is 100-120° C., the preheating time is 5-10 min, and the preheating speed is 450-550 r / min; Step 1) The mixing temperature is 100-110° C., the mixing time is 15-20 min, and the mixing speed is 550-650 r / min.
9. The preparation method according to claim 7 or 8, characterized in that: Step 2) The mixing temperature is 110-120° C., the mixing time is 20-30 min, and the mixing speed is 750-850 r / min; Step 3) The cooling time is 5 to 10 minutes, the rotation speed during the cooling process is 370 to 430 r / min; the temperature of the mixing and extrusion is 180 to 190°C.
10. Use of the high surface tension polyethylene filling masterbatch according to any one of claims 1 to 6 in high-density polyethylene polymer waterproofing membrane.
